(3GdehGgH GdQHGfjI hcfhR GdMce GdEdgjIs - (3eMehO Hf CH Hf GdWGdH eMehO Sh GdZdGhjs ((3eMeO Hf CMeO Hf Ydi Hf GdWGdH CMeO Hf GdUGje GdJTeTi GdZdGhi GdSOGOi GdhdGJi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChOY GdMQha HOGFY CSQGQg , hQcH efgG COdI JOd HfWgG Ydi eYGfi CSeGFg CeG HYO Ef c SCdJfi LedkG ef Mce GdCFeI GdLfOjI eTghQI GdJUQja eY MVQI TjNfG aLeYJ dc ajg cJGHkG hSejJg s
(3BNQgG (B:s
(3jG QH cd TF hNGdbg hQGRbg CSGdc GdKHGJ CSGdc GdMH deG JMH , hceG jfHZi Cf CMH hJe cdGefG ai gPG GdeNJUQ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3MhGagG eJBcdI HTOI hChQGbgG eJbUaI s
(3GfJgi eDdagG efgG SfI (B1247(3g` s
(3bQf GdfSN (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs